The butterflies (Lepidoptera: Papilionoidea and Hesperioidea) of the Catimbau National Park, Pernambuco, Brazil - Nobre, Carlos Eduardo B.; Schlindwein, Clemens; Mielke, Olaf H. (Zootaxa, 2008)
The first butterfly checklist for the Caatinga region and information about the taxonomic composition and seasonal structure of these butterflies is presented here. This study was conducted in the Catimbau National Park, located in the semiarid region of northeastern Brazil. The butterflies were collected from September, 2005, to August, 2006; 5 days per month, on trails exhibiting flowering plants and also by using fruit-bait traps. A total of 121 butterfly species was recorded; half of them exclusively in the rainy season, 7% exclusively in the dry season and 42% in both seasons. The species richness was low when compared to neotropical rainforest habitats, due to strong seasonality and the structurally simple vegetation. The butterfly fauna is dominated by species typical for open areas and of wide geographical distribution. No endemism was discovered.